Chronic ethanol exposure impairs alveolar leukocyte infiltration during pneumococcal pneumonia, leading to an increased bacterial burden despite increased CXCL1 and nitric oxide levels - Martins, Flávia Rayssa Braga; de Oliveira, Maycon Douglas; Souza, Jéssica Amanda Marques; Queiroz-Junior, Celso Martins; Lobo, Francisco Pereira; Teixeira, Mauro Martins; Malacco, Nathalia Luisa; Soriani, Frederico Marianetti (Frontiers in Immunology, 2023)
Ethanol abuse is a risk factor for the development of pneumonia caused by Streptococcus pneumoniae, a critical pathogen for public health. The aim of this article was to investigate the inflammatory mechanisms involved in pneumococcal pneumonia that may be associated with chronic ethanol exposure. Male C57BL6/J-Unib mice were exposed to 20% (v/v) ethanol for twelve weeks and intranasally infected with 5x104 CFU of S. pneumoniae. Twenty-four hours after infection, lungs, bronchoalveolar lavage and blood samples were obtained to assess the consequences of chronic ethanol exposure during infection. Alcohol-fed mice showed increased production of nitric oxide and CXCL1 in alveoli and plasma during pneumococcal pneumonia. Beside this, ethanol-treated mice exhibited a decrease in leukocyte infiltration into the alveoli and reduced frequency of severe lung inflammation, which was associated with an increase in bacterial load. Curiously, no changes were observed in survival after infection. Taken together, these results demonstrate that chronic ethanol exposure alters the inflammatory response during S. pneumoniae lung infection in mice with a reduction in the inflammatory infiltrate even in the presence of higher levels of the chemoattractant CXCL1.